The Effect of Using Wet Ash as a Substitute for Quicklime in Improving the Quality of Acid Mine Drainage from Coal Mining - Muhammad Fikri; Tuty Emilia Agustina; Hermansyah Hermansyah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Acid Mine Drainage (AMD) management uses the active treatment method with the addition of alkaline neutralizing chemicals such as lime (CaCO3, CaO) although the cost is more expensive. Several previous studies indicate that the application of boiler ash can increase pH and nutrient content because it is alkaline. The boiler ash used in this study came from the remaining burning of bark at a Medium Density Fiberboard industrial. Boiler ash containing water is known as Wet Ash and is strongly alkaline (pH 11.92). The purpose of this study was to analyze the effect of adding wet ash and to analyze the effectiveness of AMD processing on pH, Total Suspended Solids (TSS), Fe and Mn. The method this study: wet ash samples of 2.5 g, 5 g, 7.5 g, 10 g, 12.5 g and 15 g were mixed with 10 liters of AMD, homogenized for 10 minutes, then analyzed in the laboratory to determine its characteristics. The results of the study on the characteristics of wet ash treatment of 15 g/L with pH = 7.21, TSS = 326 mg/L, Fe = <0.018 mg/L, Mn = 6.42 mg/L is the best treatment because all parameters meet the quality standards.